Comprehensive assessment of chemical and microbial inducers for coral larval settlement across diverse coral species - Sun, Huiming; Yang, Qingsong; Dong, Junde; Li, Jie; Chen, Chang; Tang, Xiaoyu; Zhang, Ying; Ling, Juan (Frontiers in Marine Science, 2025)
IntroductionCoral restoration efforts increasingly focus on enhancing larval settlement and post-settlement survival. However, the species-specific efficacy of different settlement inducers remains inadequately understood, limiting optimization of restoration protocols.MethodsThis study systematically assessed the effectiveness of three settlement inducers—Crustose coralline algae (CCA), Chemical (CaCl2), and Microbial (Metabacillus sp. cB07)—across seven coral species, including both brooders and broadcast spawners. Larvae were exposed to gradient concentrations of each inducer to determine optimal concentrations and treatment durations. Effects on larval survivorship, metamorphosis, and settlement were measured. Post-settlement recruits treated with optimized procedures were further evaluated for metabolic rates, morphology, survival, and growth.ResultsOptimal inducer concentrations and treatment durations varied significantly among coral species, with CaCl2 (10–60 mmol/L) and cB07 (3 × 106–3 × 107 cfu/mL) showing broad-spectrum activity comparable to CCA. CCA induced the highest settlement rates (43.3%–93.3%) within 1–2 days, CaCl2 showed moderate induction (23.3%–60.3%) within 0.5–4 days, and cB07 exhibited similar efficacy (26.7%–60.0%) within 2–4 days. Biological effects differed: CaCl2 accelerated metamorphosis but lowered survival in sensitive species, while cB07 delayed metamorphosis and suppressed respiratory rates, indicating higher toxicity. Post-settlement, recruits induced by CCA and CaCl2 had higher survival and calcification rates than those induced by cB07.DiscussionThese findings underscore the necessity of tailoring settlement inducer protocols to the species-specific life histories and physiological responses of corals. Integrating metabolic and ecological insights offers practical guidelines to enhance coral restoration success amid growing environmental pressures.